Promoting to everyone, focusing on no one: The illogical promotion of the influenza vaccine. Issue 1 (March 2014) - Richards, Carly Noel; Tran, Christine; Fugh‐Berman, Adriane
<x xml:space="preserve">Abstract</x> In 2010, the Centers for Disease Control and Prevention (CDC) expanded guidelines for annual influenza vaccine to recommend universal vaccination of everyone over the age of 6 months. In 2007, the CDC partnered with Families Fighting Flu, an industry‐funded group, to create public service announcements promoting vaccination of healthy children, the segment of the population at the least risk of dying. The "everyone is at risk" message associated with universal influenza vaccination could undermine effective influenza prevention efforts. Most influenza‐related deaths and hospitalizations occur in those aged 85 and older—a population in which influenza vaccine is not very effective. Herd immunity, integral to the effectiveness of other vaccines, is difficult to achieve with influenza vaccine, which is less effective than other vaccines, and must be given annually. Controlling pandemic or non‐pandemic influenza may depend not only on vaccination but also on social distancing, handwashing, and wearing masks. Non‐vaccine infection control techniques may work against influenza and other respiratory infections. Comparative effectiveness research is needed to determine the best methods for reducing deaths and hospitalizations for influenza and pneumonia. Discussion is needed about the extent to which public health recommendations are distorted by industry relationships. Public health messaging must be evidence‐based.